AN ANALYSIS OF ENGLISH-INDONESIAN TRANSLATION PROCEDURE ON NARRATIVE TEXT - Wawat Srinawati; Yukeke Fuzianti (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2020)
The ability to translate from foreign languages is important, especially for English Education which is closely related to foreign languages. Translation is needed because students have to get information and knowledge for everyday life. The objective of this research is to describe the English-Indonesian translation procedures were used in translating narrative text. This research has used descriptive qualitative method. This research has been conducted at STKIP Muhammadiyah Bogor with the population of 6th semester students of English Education Department and consists of 5 samples taken using a purposive sampling technique. This study used students’ translation results and interview for data collecting technique. The result of this study, the writer found 266 translation procedure has used by participant, consist of transposition 159 cases, modulation 51 cases, adaption 11 cases, transference 0 case, addition 22 cases, reduction 15 cases, descriptive equivalent 5 cases, and naturalization 3 cases, and the difficulty in translating the text is the discovery of new vocabulary and the arranged of a word into a sentence.